Leisure Preferences of Russian Specialists as a Factor of Human Potential Building - Natalia V. Latova (Социологический журнал, 2022)
The article analyzes the leisure preferences of Russian workers with an emphasis on specialists as a special professional group. Human potential theory is chosen as the main theoretical framework. Based on R. Stebbins’ concept, a typology of modern leisure practices in terms of their impact on human potential is offered. The analysis of data from the all-Russian survey conducted in October 2018 by the Institute of Sociology of FCTAS RAS leads to the conclusion that compared to other workers specialists more often and more fervently choose those types of leisure activities that contribute to the development of their human potential. At the same time, advanced leisure practices are more popular among specialists from the following subgroups: women, young people, city dwellers, and those who consider themselves to be in good health. In addition to these characteristics, external accessibility and internal demand for knowledge also have positive effects. When comparing data from 2018 and 2008, there are some apparent positive shifts in professionals’ leisure preferences. However, we also see a decrease in the rate of growth in professionals’ interest towards advanced leisure practices. In addition, by 2018, in terms of leisure time spent on education, specialists fell behind such groups as entrepreneurs, the self-employed and managers of various levels, who demonstrate a stronger focus on building human potential. Thus, Russian specialists are ahead of most Russians when it comes to the human potential criterion, but their involvement in educational activity in their leisure time (especially in health-preserving behavior) is lower than that of entrepreneurs/self-employed/managers. This calls into question whether this professional group’s characteristics are adequate for the current post-industrial trends.